2019
DOI: 10.1096/fj.201802723r
|View full text |Cite
|
Sign up to set email alerts
|

Statin‐dependent modulation of mitochondrial metabolism in cancer cells is independent of cholesterol content

Abstract: Statins, widely used to treat hypercholesterolemia, inhibit the 3‐hydroxy‐3‐methylglutary1‐coenzyme A reductase, the rate‐limiting enzyme of de novo cholesterol (Chol) synthesis. Statins have been also reported to slow tumor progression. In cancer cells, ATP is generated both by glycolysis and oxidative phosphorylation. Mitochondrial membrane potential (ΔΨ), a readout of mitochondrial metabolism, is sustained by the oxidation of respiratory substrates in the Krebs cycle to generate NADH and flavin adenine dinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…Additionally, Sim, is a cholesterol-lowering agent, and recently has also been reported to participate in the suppression of glycolysis and Sora resistance. Christie et al found that statins can partially block the utilization of glycolytic ATP [46]. Huang et al found that the combination of pitavastatin and paclitaxel can significantly decrease the glycolytic rate in renal carcinoma [47].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Sim, is a cholesterol-lowering agent, and recently has also been reported to participate in the suppression of glycolysis and Sora resistance. Christie et al found that statins can partially block the utilization of glycolytic ATP [46]. Huang et al found that the combination of pitavastatin and paclitaxel can significantly decrease the glycolytic rate in renal carcinoma [47].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial hyperpolarization represents an early and reversible step in T cell activation and apoptosis [79]. Transient high ΔΨ m values have also been described by synthetic cannabinoids in human proximal tubule cells [80], by statins (lovastatin and simvastatin), which increased the ΔΨ m in HepG2 and Huh7 human hepatocarcinoma cells and HCC4006 human lung adenocarcinoma cells [81], and by honokiol, which induced in bladder cancer cells and increase of ΔΨ m and ROS formation, and at high doses apoptotic cell death [82]. Hyperpolarization of ΔΨ m was furthermore shown with protamine sulfate [83] and graphene oxide (a marker for air pollution) [84].…”
Section: Stress and Calcium Signalingmentioning
confidence: 98%
“…Atorvastatin also induced autophagy and inhibited proliferation on prostate cancer cells through up-regulation of miR-182 [19]. Atorvastatin has been identified through modulating mitochondrial metabolism to interfere cancer process [20]. However, any other mechanism implicated in the anti-tumor effect of atorvastatin has not been clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%